Diagnosis of carbon monoxide exposure in clinical research and practice: A scoping review - Phil Moss; Natasha Matthews; Rosalie McDonald; Heather Jarman (PLoS ONE, 2025)
Objective To undertake a scoping review to identify methods and diagnostic levels used in determining unintentional, non-fire related carbon monoxide exposure. Design Online databases and grey literature were searched from 1946 to 2023 identifying 80 papers where carbon monoxide levels were reported. Results 80 papers were included; 71 research studies and 9 clinical guidelines. Four methods were described: blood carboxyhaemoglobin (arterial or venous blood analysis), carbon monoxide oximetry (SpO2), expired carbon monoxide, and ambient carbon monoxide sampling. Blood analysis methods predominated (60.0% of the papers). Multiple methods of measurement were used in 26 (32.5%) of the papers. Diagnostic levels for carboxyhaemoglobin were described in 54 (67.5%) papers, ranging between 2% and 15%. 26 (32.5%) papers reported diagnostic levels that were adjusted for the smoking status of the patient. Conclusions Four methods were found for use in different settings. Variability in diagnostic thresholds impairs diagnostic accuracy. Agreement on standardised diagnostic levels is required to enable consistent diagnosis of unintentional, non-fire related carbon monoxide exposure.